The Summa Halensis Doctrines and Debates - Schumacher, Lydia (Veröffentlichungen des Grabmann-Institutes zur Erforschung der mittelalterlichen Theologie und Philosophie, 2020)
The Summa Halensis (1236-45) was collaboratively authored by the founding members of the Franciscan school at Paris and represents not only the first official statement of Franciscan thought but also a defining text for the field of systematic theology. This volume brings together leading scholars who explore the diverse doctrines and debates, with a view to highlighting its innovativeness and influence on subsequent generations.